AB0143 Implication of osteonectin on cardiovascular risk in axial spondyloarthritis: a serological and genetic study. (12th June 2018) - Genre, F.; Rueda-Gotor, J.; Remuzgo-Martínez, S.; Irure-Ventura, J.; Corrales, A.; Mijares, V.; Portilla, V.; Blanco, R.; Rodríguez-Rodríguez, L.; Hernández, J.L.; Llorca, J.; Ocejo-Vinyals, J.G.; et al.
Abstract : Background: Cardiovascular (CV) disease and atherosclerosis are common causes of morbidity in axial spondyloarthritis (axSpA), 1 a disease characterised by changes in the osteoproliferative process. A dysregulation in the molecules involved in bone remodelling could also affect the atherosclerotic process, since both processes are linked. 2 3 Osteonectin (ON), a key molecule in bone homeostasis, 4 was associated to obesity, insulin resistance and diabetes. 5 Objectives: Since the exact role of ON on CV risk in axSpA has not been elucidated yet, we evaluated its role in the development of subclinical atherosclerosis and its association with CV risk factors in axSpA patients at the serological and genetic level. Methods: 171 axSpA patients fulfilling the classification criteria for axSpA 6, 7 and 84 controls were included in this study. Serum ON levels were measured by multiplex assays. Carotid ultrasound was performed to evaluate the presence of markers of subclinical atherosclerosis. Five ON polymorphisms (rs1054204 [G/C], rs11950384 [G/A], rs13182103 [A/G], rs11745387 [G/A] and rs4958487 [A/G]) were selected by tagging and genotyped using TaqMan assays. Results: No difference was observed in ON levels between axSpA and controls. Serum ON and CRP levels at study positively correlated in axSpA (p=0.008). Higher ON levels were observed in men, smokers and patients with an atherogenic index indicative of dyslipidemia (p=0.008, 0.01 and 0.001, respectively). No association was found between ON and subclinical atherosclerosis in axSpA. Interestingly, we disclosed that the presence of the A allele of rs13182103 and rs11950384 ON polymorphisms led to lower ON serum levels in axSpA (p<0.05). Furthermore, the presence of the A allele of rs13182103 was linked to a later diagnosis of axSpA when compared to those patients bearing the G allele (p=0.002). Conclusions: Our results show that ON is linked to inflammation and CV risk factors in axSpA and suggest that the A allele of rs13182103 and rs11950384 ON polymorphisms may have a protective effect in axSpA, leading to reduced ON serum levels and later diagnosis of the disease. These data support an implication of ON in the development and progression of atherosclerotic disease in axSpA. References: [1] Joint Bone Spine2014;81(1):57–63. [2] Clin Chim Acta2015;438:401–14. [3] Arterioscler Thromb Vasc Biol2001;21(12):1998–2003. [4] J Bone Miner Res2015;30(4):723–32. [5] Int J Clin Exp Med2015;8(10):19290–6. [6] Ann Rheum Dis2009;68:777–83. [7] Arthritis Rheum1984;27:361–8. Acknowledgements: FG is a recipient of a Sara Borrell post-doctoral fellowship from Instituto de Salud Carlos III (ISCIII, Spain), co-funded by European Social Fund (ESF, CD15/00095). SR-M is supported by funds of RETICS Program (RD16/0012/0009, ISCIII, co-funded by European Regional Development Fund, ERDF). RL-M is a recipient of a Miguel Servet type I fellowship from ISCIII, co-funded by ESF(CP16/00033). VM is supported by funds of a Miguel Servet type I (CP16/00033)(ISCIII, co-funded by ERDF). Disclosure of Interest: None declared